Pengaruh model pembelajaran kooperatif terhadap keterampilan berpikir kritis dan kreatif dalam pembelajaran IPA pada siswa Sekolah Dasar - Twiningsih, Anik; Retnawati, Heri; Cahyandaru, Pramudya (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2022)
Many implementations of cooperative learning have been carried out, but the selection of cooperative learning models still needs to be investigated. This study aims to determine the effect of cooperative learning models such as the Group Investigation (GI) model, Student Team Achievement Division (STAD), and Jigsaw on critical and creative thinking skills in science learning in fourth-grade students in elementary school. The research uses a quantitative research approach. The research sample was randomly selected from 75 fourth-grade elementary school students. Data were collected by using the critical and creative thinking skills test method. The test instrument is structured with indicators of critical and creative thinking variables which are applied in the study of science learning. The research instrument is in the form of a description test that has met the validity and reliability tests. The technique of data analysis was done with a Multivariate Analysis Of Variance. The results show that the critical and creative thinking skills obtained sig. of 0.001 <0.05, which means that the cooperative learning model significantly affects critical and creative thinking skills multivariate. Meanwhile, post hoc testing shows that the GI model is superior for improving critical and creative thinking skills. Keywords:  Cooperative learning model, Critical thinking skills, Creative thinking